Mini photopheresis for refractory chronic graft‐versus‐host disease in children and adolescents. Issue 11 (6th October 2018) - Verdú‐Amorós, Jaime; Woessmann, Wilhelm; Maecker‐Kolhoff, Britta; Schulz, Ansgar; Strauss, Gabriele; Bein, Gregor; Hackstein, Holger
Abstract : BACKGROUND: Extracorporeal photopheresis (ECP) has been established to treat graft‐versus‐host disease. Our mini ECP technique (mini‐ECP) allows for treatment of patients with GVHD and contraindications for classical ECP or low body weight. The safety and efficacy of applying ECP for the long‐term treatment of chronic GVHD (cGVHD) have not been described. STUDY DESIGN AND METHODS: A retrospective analysis of mini‐ECP treatments for children and adolescents with cGVHD was performed. Mini‐ECP with 100 to 200 mL of whole blood was used to treat 14 patients. The median age at the start of treatment was 7 years (range, 1‐17 years), and median body weight was 20 kg (range, 8‐53 kg). A total of 703 mini‐ECP treatments was performed. The median number of treatments per patient was 35 (range, 8‐129), and median treatment duration was 11 months (range, 1.4‐28.5 months). RESULTS: Mini‐ECP was well tolerated. Four adverse events occurred in three patients, and two of them were related to the ECP procedure. Complete or partial responses were observed in 10 patients. Steroids were discontinued in seven patients and tapered in three others. Responses were seen in the skin, mouth, gastrointestinal tract, and eyes. CONCLUSION: Mini‐ECP represents a less invasive ECP alternative for low‐body‐weight patients with cGVHD and contraindications for apheresis.